Study of the qualitative composition and determination of the quantitative content of phenolic compounds by the HPLC method in the flowers of Celosia cristata (L.) Kuntze - Zhuravel, Iryna; Deyneka, Alina (Annals of Mechnikov’s Institute, 2022)
Introduction. Celosia cristata (L.) Kuntze is one of the 60 representatives of the Amaranthaceae L. family. It was brought to Europe in the middle of the 16th century. It is a perennial herbaceous plant with juicy straight ribbed stems of green or brown-green color. The leaves are green with purple spots or completely brown, located on short petioles. The leaf blade is oval-lanceolate or linear-lanceolate with a pointed tip. The flowers are small, silvery, collected in the apical inflorescence of panicles, resembling a cock’s comb. The color of the flowers depends on the variety and can be from yellow with a golden tint to burgundy. The fruit is a ball-shaped box with numerous small, black, shiny seeds. Cockscomb (Celosia cristata (L.) Kuntze) is grown in Ukraine mainly as an ornamental plant. The chemical composition of this plant is represented by saponins, flavonoids, betalains, amino acids, tannins, and alkaloids. Nitrogen-containing pigments betacyanins and betaxanthins were isolated from the inflorescences of Celosia cristata(L.) Kuntze. It is also known that flowers contain carbohydrates, amino acids and phenolic compounds. Saponins cristain and cellosins A, B, C and D, semenoside A, glycoproteins, β-sitosterol and stigmasterol were isolated from the seeds of this plant. However, the chemical composition of the flowers of this plant has not been studied enough. Pharmacological studies conducted by foreign scientists have shown that celosia combis is characterized by anti-inflammatory, immunostimulating, antinociceptive, antitumor, hepatoprotective, antidiabetic, antioxidant, wound-healing, antiviral, antimicrobial, anthelmintic activity. In the folk medicine of Mexico and China, the seeds of the combed celosia are used for hemorrhoids, headaches, leucorrhoea, bacterial skin diseases, cataracts, hypertension, leaves - for liver diseases. Phenolic compounds are an important group of compounds of secondary plant synthesis. Flavonoids and hydroxycinnamic acids are the most common phenolic compounds with a wide spectrum of action. They improve the condition of capillary walls, have a positive effect on the motility and secretory function of the gastrointestinal tract, have antispasmodic, wound healing, anti-inflammatory, hypoglycemic, antitumor, bactericidal, antiradical, diuretic activity. Little-studied plants that have long been used in traditional medicine can become a new source of phenolic compounds. Among such plants can be attributed to the combed celosia. The purpose of the work was to study the qualitative composition and determine the quantitative content of phenolic compounds by HPLC. Materials and methods. Air-dried, crushed flowers of Сelosia cristata (L.) Kuntze were used for the experiment. The raw materials were harvested in 2019-2021 in the Kharkiv region. The study of the qualitative composition and determination of the quantitative content of phenolic compounds was carried out by the HPLC method. Results and their discussion. According to the results of the experiment, 11 compounds of phenolic nature were identified in the flowers of Сelosia cristata (L.) Kuntze, in particular 8 phenolic acids, of which 4 belonged to hydroxycinnamic (caffeic, p-coumaric, ferulic and rosmarinic) acids, as well as 3 flavonoids (rutin, luteolin, quercetin). The total content of phenolic compounds identified in the flowers of Сelosia cristata (L.) Kuntze was 1780.15 mg/kg. Quantitatively, this raw material was dominated by hydroxycinnamic acids (964.65 mg/kg), the content of which accounted for more than 50% of the total content of identified phenolic compounds in the flowers of Сelosia cristata (L.) Kuntze. Flavonoids in the studied sample contained almost 1.5 times less - 652.99 mg/kg. The dominant compound in the flowers of Сelosia cristata (L.) Kuntze was p-coumaric acid. Its content was 866.70 mg/kg, which was almost half of the content of all identified compounds. Among the flavonoids in the flowers of Сelosia cristata (L.) Kuntze, rutin prevailed. 343.73 mg/kg of this compound was accumulated, which was almost half of the content of flavonoids in the studied raw materials. The amount of luteolin in the flowers of the combed celosia was somewhat less - 252.40 mg/kg. Veratric acid accumulated 120.99 mg/kg. The content of p-hydroxybenzoic, caffeic, lilac, ferulic, rosmarinic, salicylic acids and quercetin did not exceed 60 mg/kg. Conclusions. Using the HPLC method, 11 phenolic compounds with a total content of 1780.15 mg/kg were identified in the flowers of Сelosia cristata (L.) Kuntze, among which hydroxycinnamic acids dominated quantitatively. It was established that p-coumaric acid was the dominant compound in this raw material. Among flavonoids, rutin prevailed (343.73 mg/kg). The obtained results of the experiment will be used as a basis for the development of medicinal products based on the flowers of the combed celosia. Keywords: HPLC, quantitative, phenolic compounds,flowers of Celosia cristata